The Hydractinia cell atlas reveals cellular and molecular principles of cnidarian coloniality - David A. Salamanca-Díaz; Helen R. Horkan; Helena García-Castro; Elena Emili; Miguel Salinas-Saavedra; Alberto Pérez-Posada; Maria Eleonora Rossi; Marta Álvarez-Presas; Rowan Mac Gabhann; Paula Hillenbrand; Febrimarsa; Camille Curantz; et al. (Nature Communications)
Abstract Coloniality is a widespread growth form in cnidarians, tunicates, and bryozoans, among others. Colonies function as single physiological units despite their modular structure of zooids and supporting tissues. A key question is how structurally and functionally distinct colony parts are generated. In the cnidarian Hydractinia symbiolongicarpus, colonies consist of zooids (polyps) interconnected by stolons attached to the substrate. Using single-cell transcriptomics, we profiled ~200,000 Hydractinia cells, including stolons and two polyp types, identifying major cell types and their distribution across colony parts. Distinct colony parts are primarily characterised by unique combinations of shared cell types and to a lesser extent by part-specific cell types. We identified cell type-specific transcription factors (TFs) and gene sets expressed within these cell types. This suggests that cell type combinations and occasional innovations drive the evolution of coloniality in cnidarians. We uncover a novel stolon-specific cell type linked to biomineralization and chitin synthesis, potentially crucial for habitat adaptation. Additionally, we describe a new cell type mediating self/non-self recognition. In summary, the Hydractinia cell atlas provides insights into the cellular and molecular mechanisms underpinning coloniality.